Pengukuran Kesenjangan Digital di Institusi Pemerintah Daerah (Studi Kasus: Pemerintah Kota Semarang) - Pertiwi Windasari, Ike (Jurnal Sistem Komputer, 2011)
The rapid growth of information and communication technology (ICT) facilitate human activity. Along with this rapid development, emerge a gap between individuals who have access to technology and those whose not. This is what we called the digital divide. The main challenges of e-government development are the ability and readiness of management not only the technology. The skill divide between human resources in the government will certainly affect the implementation of e-government in Indonesia.The purpose of this study was to determine the factors that influence the digital divide between individuals in the government, to measure the condition of the digital divide between the current individual in government.